2014
DOI: 10.1128/aac.03817-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Antifungal Combinations against Biofilms and Planktonic Forms of Clinical Trichosporon asahii Isolates

Abstract: T richosporon species can cause biofilm-associated infections related to indwelling medical devices, especially intravenous catheters, and unacceptable mortality rates have been reported despite the administration of antifungal treatments (1). Trichosporon asahii can form biofilms with structured microbial communities in vitro, embedded within an extracellular matrix, with significantly increased resistance to antifungal compounds (2, 3), which might ultimately lead to clinical treatment failure. Antifungal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
(4 reference statements)
3
9
0
Order By: Relevance
“…On the other hand, T. inkin biofilms were tolerant to higher concentrations of all antifungals tested. Similar results were found by Di Bonaventura et al (2006), Iturrieta-González et al (2014) and Liao et al (2014), who reported that, although Trichosporon spp. planktonic cells were susceptible to voriconazole and fluconazole, their biofilm counterparts were resistant to azoles, amphotericin B and caspofungin.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…On the other hand, T. inkin biofilms were tolerant to higher concentrations of all antifungals tested. Similar results were found by Di Bonaventura et al (2006), Iturrieta-González et al (2014) and Liao et al (2014), who reported that, although Trichosporon spp. planktonic cells were susceptible to voriconazole and fluconazole, their biofilm counterparts were resistant to azoles, amphotericin B and caspofungin.…”
supporting
confidence: 87%
“…Biofilms produced by Trichosporon spp. also presented higher tolerance to antifungals (Di Bonaventura et al, 2006;Iturrieta-González et al, 2014;Liao et al, 2014;Sun et al, 2012). Data from the present study reveal that planktonic cells showed susceptibility to azoles and resistance to amphotericin B and caspofungin.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Liposomal amphotericin B had the highest activity against biofilms formed by isolates with acquired resistance (the P value was not significant) or intrinsic resistance (P Ͻ 0.05) to echinocandins; this finding is consistent with other studies, where conventional amphotericin B had high anti-biofilm activity, even against non-Candida isolates (25)(26)(27)(28)(29). However, we observed that biofilms formed by C. tropicalis isolates were highly resistant to liposomal amphotericin B, which was unable to achieve an 80% reduction in the metabolic activity of the biofilm.…”
Section: Resultssupporting
confidence: 90%